INTENSITAS DAN PREVALENSI EKTOPARASIT BERDASARKAN STADIA UMUR IKAN PADA IKAN NILA (Oreochromis niloticus) DI BALAI PENGEMBANGAN BUDIDAYA IKAN AIR TAWAR (BPBIAT) KOTA CIREBON, JAWA BARAT - Alfiyani, Nur; Sutaman; Umi Hartanti, Ninik (Universitas Pancasakti Tegal, 2023)
The aim of this research is to identify ectoparasites and determine the value of the intensity and prevalence of ectoparasites in the egg stage, larval stage, adult stage and parent stage on tilapia (Oreochromis niloticus) at Freshwater Fish Cultivation Development Center (BPBIAT) Cirebon City, West Java. The method used in this study is observation. Fish sampling was taken randomly as much as 5% with different of the each stage, in the age stage, larval stage, adult stage, and parent stage. The results showed that obtained of the parasite Trichodina sp, Dactylogyrus sp, Gyrodactylus sp, and Cichlidogyrus sp. Highest intensity of ectoparasites was Trichodina sp as much as 6,3 and lowest intensity of ectoparasites was Cichlidogyrus sp as much as 0,1. Highest intensity of ectoparasites was parent stage as much as 6,6 and lowest intensity of ectoparasites was egg stage as much as 0. Highest prevalence of ectoparasites was parent stage as much 66,67% and lowest prevalence of ectoparasites was egg stage as much as 0%.